ANALISIS YURIDIS AGUNAN BERUPA ASET KRIPTO DALAM PENERAPAN PRINSIP 5C PEMBERIAN KREDIT PERBANKAN - Kirana, Anggun (JURNAL AKTA YUDISIA, 2022)
AbstractThis research will examine from a juridical perspective whether crypto assetscan be used as collateral in the application of the 5C principles of bankingcredit issuance. This research is a normative legal study that employs astatutory approach. The primary legal materials used include the Civil Code,Law Number 10 of 1998 concerning Amendments to Law Number 7 of 1992on Banking, Law Number 32 of 1997 on Commodity Futures Trading, LawNumber 42 of 1999 on Fiduciary Guarantees, and secondary legal materialssuch as books, journals, and the findings of other research related to the issue.The results of this study indicate that crypto assets can be used as collateral inbanking credit issuance, either through pawn or fiduciary institutions, each ofwhich has its own characteristics. Therefore, the appropriate collateralinstitution will depend on the preferences of the debtor and the creditor. It isimportant to identify legal risks and other associated risks, such as pricefluctuations, so that crypto assets can be used as additional collateral ratherthan primary collateral.Keywords: Aset Kripto, Prinsip 5C, Kredit Perbankan